A Community-Based, Focused-Deterrence Approach to Closing Overt Drug Markets A Process and Fidelity Evaluation of Seven Sites - Saunders, Jessica (RAND Corporation, 2016)
Overt drug markets are often associated with violence and property crime, as well as lower quality of life for nearby residents. This process evaluation describes how well seven jurisdictions adhered to a Bureau of Justice Assistance strategy to reduce overt drug markets, as well as the barriers they encountered and the lessons learned from their experiences.